COMPARISON OF VERAPAMIL AND CIMETIDINE FOR THEIR EFFECTS ON VOLUME AND ACIDITY OF CARBACHOL INDUCED GASTRIC SECRETION IN FASTING RABBITS - Jan, Muhammad; Orakzai, Shaukat Ali; Tariq, Shafique; Javid, Muhammad; Ahmad, Shafiq; Haroon, Muhammad; Qamar, Muhammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: Peptic ulcer is a common ailment for which over production of gastric acid is the main cause. This study was undertaken to find out the effects of Calcium channel blocker Verapamil and Cimetidine on volume and acidity of Carbacol induced gastric section, free and total acidity of carbachol induced gastric secretion and their effects were also compared. Methods: Thirty rabbits of local breed weighing 1-1.5kg were used. The animals were kept on fasting for 48 hours after which the pylorus of each was ligated. Verapamil 10mg/kg, Cimetidine 2.5 mg/kg and Carbachol 600Î¼g/kg body weight were administered intrapertoneally in pylorus ligated rabbits. Results: It was found that Verapamil reduced the volume, free and total acidity of gastric secretion, which were statistically highly significant when compared with Carbachol (P<0.001). Cimetidine also had the same effects. when the difference of means values brought about by verapamil were compared with those of Cimetidine, all these differences were found statistically non significant, indicating that Verapamil has similar effect as that of Cimetidine on all parameters included in study. Conclusion: Verapamil has significant effect on volume and acidity of carbachol induced gastric secretion. Keywords: Verapamil, Cimetidine, Carbachol, Gastric Secretion, Rabbit, Stomach, Acidity